Exploring the self-reported physical fitness and self-rated health, mental health disorders, and body satisfaction among Chinese adolescents: A cross-sectional study - Shi, Chongyan; Yan, Jin; Wang, Lei; Shen, Hejun (Frontiers in Psychology, 2022)
Background: Physical activity (PA) and Physical fitness (PF) have received tremendous attention in the field of physical and mental health. However, limited attention has been given to the associations of self-reported physical fitness with some health-related outcomes. Given the influence of COVID-19 in many regions of China, this study was conducted via a self-reported questionnaire. Purpose: The present cross-sectional study was aimed at delving into the relationship between of self-reported physical fitness with self-rated health, depression, anxiety, and body satisfaction in adolescents. 3807 study participants from 12 public schools in South-eastern China were recruited and 2407 of them provided valid data on variables that this study needed for analysis. Method: Study participants were asked to self-report their sociodemographic factors (e.g., sex, grade, age), independence, and outcomes. Generalized linear models were used to explore the associations of self-reported physical fitness (comprising general physical fitness, cardiorespiratory fitness, muscular strength, speed and agility, and flexibility) with depression, anxiety, and body satisfaction. A total of 2407 children and adolescents with a mean age of 13.82 (±2.1) years were included in the final study analysis. Results: Higher self-reported levels of general physical fitness and cardiorespiratory fitness were associated with better self-rated health, and body satisfaction but with lower risks of depression and anxiety. Conclusion: The current study offered evidence on the roles of self-reported physical fitness and health-related outcomes. To facilitate health in children and adolescents, advocating fitness education and promotion could be a feasible approach.